Administrative management and teaching performance. Educational Institution No. 6073 “Jorge Basadre”, Lima. - Loreña León, Luz María (2025)
The objective of this study is to identify whether there is a relationship between administrative management (variable 1) and teacher performance (variable 2) at Educational Institution 6073 in the Villa María del Triunfo district of Lima. This study uses a quantitative, cross-sectional, ordinal-level study, a hypothetical-deductive method, and a descriptive correlational design. We used a sample of teachers. Validated by the judgment of three experts, the instrument consisted of Likert-type rating scale questionnaires, each with 32 items based on its four dimensions. The results obtained with descriptive and inferential statistics, using Spearman's Rho coefficient, show a direct and significant correlation between the two study variables. This also illustrates the importance of examining administrative management in schools for the organization and good teacher performance, ensuring that each teacher fulfills their roles and responsibilities, and achieving efficient and effective results for the community.